Centralized vs Decentralized Tourism Policies: A Spatial Interaction Model Framework - Guido Candela; Maurizio Mussoni; Roberto Patuelli (European Regional Science Association (ERSA), 2015)
The choice of centralizing tourism policies at the national level or, on the contrary, of decentralizing them at the local level is widely discussed in the literature, which highlights the related pros and cons. In fact, the simultaneous role of originator and attractor of tourism of each spatial unit may imply a range of complex and competing interests at various geographical scales. At any one time, organizations at the national, regional and local level are actively engaged in promoting tourism destinations in order to attract tourists. Nevertheless, potential competition/complementarity between regions in terms of their attractivity factors may imply a range of complex and competing interests at various geographical scales. In particular, in a framework of regional competition, a central (national) policy may be necessary to offset or coordinate the clashing regional interests. An increasingly important force of attraction for tourists (both domestic and international) is cultural tourism. For this reason, national and regional governments make great efforts to implement effective cultural tourism policies, for example to obtain an official certification for their historical/cultural attractions, like UNESCO?s World Heritage Sites (WHS) list. The WHS endowment of the regions surrounding a tourism destination may have a negative effect on its inflows of tourists (Patuelli et al. in J Geogr Syst 15:369?402, 2013). Indeed, tourists consider, in forming their travelling choices, the WHS endowment of alternative destinations, generating a phenomenon of spatial substitution (competition). This paper focuses on the choice between implementing tourism governance and policymaking at the central (national) or at the local (regional) level. The issue is raised by the following problem: (1) regional endowment (i.e., attractivity factors) may positively influence arrivals to tourism destinations, providing a justification for local policies (e.g., lobbying towards the national government for obtaining UNESCO?s WHS designations); (2) however, regional competition may reduce the positive direct effect, so that it may be necessary the intervention of the central (national) policy maker, to ?compensate? or ?correct? the local (regional) policies. The issue concerns the choice of how managing regional spillovers: regions could use their attractivity factors to gain a competitive advantage over other regions, but at the same time they risk damaging the national interest to attract tourists and increase the international market share. It is therefore critical to correctly balance and coordinate the tourism policies between the national and regional levels in order to effectively manage the regional endowment to cater to the cultural tourism demand. We stress that more profound insights into the problems and challenges of (de)centralized tourism policies can be gained by examining the national-regional choice, and in particular by using as a modelling framework, the ?normative? spatial interaction model.
Keywords: P48; L83; R12; R58; Z10; 330; tourism governance; tourism policies; spatial interaction model